2016
DOI: 10.15850/ijihs.v4n1.679
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Prostate Specific Antigen and Gleason Score in Relation to Imunohistochemistry Features in Prostate Adenocarcinoma Patients in Dr. Hasan Sadikin General Hospital

Abstract: Objective: To review the correlation between prostate specific antigen (PSA) and Gleason score and Cav-1 for diagnosing prostate adenocarcinoma. Methods: Data were collected from one hundred fifty-nine patients with prostate adenocarcinoma at the Department of Urology, Dr. Hasan Sadikin General Hospital in the period of January 2008-December 2010. The PSA levels were measured and classified into <4 ng/ml, 4-10 ng/ml, and >10 ng/ ml. The results were then analyzed and compared to the imunohistochemistry (caveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Yarney et al [21] also stated that more (poorly differentiated) lethal tumor stage is likely to produce less PSA serum. Our results share similar sentiments with Glady et al [12] as no statistical association between serum PSA and tumour grade has been identified ( Table 2, p-value = 0.539). This agreed, however, with the statement that poorly differentiated adenocarcinoma results in less PSA serum than adequately differentiated adenocarcinomas ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yarney et al [21] also stated that more (poorly differentiated) lethal tumor stage is likely to produce less PSA serum. Our results share similar sentiments with Glady et al [12] as no statistical association between serum PSA and tumour grade has been identified ( Table 2, p-value = 0.539). This agreed, however, with the statement that poorly differentiated adenocarcinoma results in less PSA serum than adequately differentiated adenocarcinomas ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Serum PSA has been suggested to produce 70% false positives, rendering it an ineffective method for diagnosing prostate cancer [20]. According to Glady et al, [12], serum PSA has limitations which questioned its efficacy. Their report had it that serum PSA did not reliably predict tumour grade at metastatic stage.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to different factors such as efficient public health programmes on prostate cancer ensuring that patients visit the health center regularly for screening and the accuracy in the diagnosis from our facility. The use of serum PSA has also increased the prevalence rate in most countries [10]. There has been a decrease in prevalence rate to 31.12% in Asia [11] whiles the opposite has been recorded in the Arab world [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that serum PSA churns out 70% false positives, making it an unreliable tool for diagnosing prostate cancer [18]. According to Glady et al, [10], serum PSA has limitations which questioned its efficacy. In their assertion, they postulated that serum PSA does not reliably predict tumour grade of stage of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of serum PSA in most countries has also raised increased detection rate and concomitant increased prevalence rate [11,12]. Some literature findings show that the prevalence rate in Asia has decreased to 31.12% [13], while in the Arab world the opposite has been reported [14].…”
Section: Discussionmentioning
confidence: 99%